A Discussion on Finding the Opportunity of Intelligent Transportation Systems (ITS) Implementation in Peru Based on Economics - Franklin Ore Areche; Isaac John Ibanga; Onibode Bamidele (The Indonesian Institute of Science and Technology Research, 2023)
The means of transport are major points in a country's infrastructure and economic development, so it is important to analyse its methods and obstacles for further interventions. This study aims to discuss the Opportunity of Intelligent Transportation Systems (ITS) implementation in Peru based on the Economy. The study was subdivided into parts. In the first part briefly reviewed the system of transportation in other countries in comparison with Peru. It further discusses the technologies influencing ITS development, the barriers to ITS implementation as well as Strategies for Implementing ITS in Peru. Three research questions guided that study and an expo facto research design was adopted as the study utilizes secondary data. The study does not consider human participation, rather, kinds of literature and reports of financial status and projections were collected, collated, utilized, and analysed for the study. The study revealed that the worldwide ITS issues is more controlled that that witnessed in Peru as the issue fluctuates between 0 and 100%. Peru has a promising economy which ITS will be implemented with ease. It is concluded that a comprehensive analysis taking into account a range of economic, social, and technological factors will be required to fully understand the potential and challenges of ITS implementation in the country.